Sıçan overinde iskemi reperfüzyon hasarında diazoksidin koruyucu etkisinin incelenmesi / Investigation of diazoxidine protective effect in rat ovary ischemia reperfusion injury - SARIOĞLU YARDIMCI, Elif Aslı (Bezmialem Vakıf University, 2017)
Objective: To investigate the efficacy of diazoxidine to prevent ischemia / reperfusion tissue damage in rats that we experimentally modeled as ovary-torsion. Materials and Methods: In this randomized controlled experimental study, Wistar Albino type of female rats in 35 reproductive cycles were used. It was divided into 7 groups randomly, as each group with 5 people. Group 1 (S): sham group, only laparotomy group. Group 2 (I): group with ischemia for 3 hours. Group 3 (I / R3): group that was reperfused 3 hours after ischemia for 3 hours. Group 4 (I / R3 + D): group given diazoxide after 3 hours reperfusion. Group 5 (I / R24): group reperfused 24 hours after ischemia for 3 hours. Group 6 (I / R24 + D): group given diazoxide after 24 hours reperfusion. Group 7 (DMSO): group only treated with DMSO because diazoxide dimethyl sulfoxide (DMSO) was used as solvent in the other groups, in order to provide standardization. After the procedure, the blood samples were taken from all groups and bilateral oophorectomy was performed. DNA damage was assessed via the Comet assay method. Tissue TAS, TOS, OSI, catalase, plasma TAS, TOS and OSI from the oxidative stress parameters were studied. In addition, apoptosis was assessed via western blot method. Results : According to the ischemia group, we observed that the DNA damage decreased significantly in the group that we gave diazoxide after 3 hours reperfusion (p = 0.04). When we looked at the oxidative stress parameters, we evaluated that tissue TOS in the group that gave the drug after 3 hours of reperfusion and in the group that gave the drug after 24 hours of reperfusion was statistically significantly lower than the ischemic group (p = 0.04, p = 0.04). We found that the tissue OSI was significantly higher in the control group that we gave DMSO for diazoxidine dissolution compared to the group that gave diazoxide after 3 hours reperfusion (p = 0.05). While plasma TOS and plasma OSI were significantly lower in the control group than in the ischemia reperfusion group for 3 hours and the ischemia reperfusion group for 24 hours (p = 0.01, p = 0.03), we found a statistically significant difference between the control group and the drug group after 3 hours reperfusion (P = 0.00). In addition, we deduced the 3-hour reperfusion-induced diazoxide group as significantly lower than the 3-hour reperfusion group (p = 0,01). We also found a statistically significant difference between the 3 hour reperfusion group and the control group that gave DMSO for dissolution of diazoxide (p = 0.03). After 3 hours of ischemia, diazoxide was found to be significantly lower than that of group given diazoxide 24 hours after reperfusion (p = 0,00) and 24 hours after reperfusion (p = 0.03). At the same time, we observed that plasma TOS and OSI were significantly higher in the 24 hour reperfusion group without drug than in the DMSO group (p = 0.01). We could not find any statistically significant difference between the groups in terms of plasma TAS, tissue TAS, tissue catalase. Conclusion: Our findings show that diazoxidine partially reduces oxidative stress in relation to time in ovary ischemia reperfusion injury. It can be said that the diazoxidine effect is better as inversely proportional to the duration of reperfusion. Although clinically, the effective treatment of ovary-torsion is surgical correction of the torsion, damage can be reduced by the addition of antioxidant substances such as diazoxide, which will be applied in this phase in addition to surgical intervention.

{{abstract}}
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Gynecology and Obstetrics, Istanbul, 2017
Keywords: Kadın Hastalıkları ve Doğum = Obstetrics and Gynecology